2013
DOI: 10.1002/cb.1417
|View full text |Cite
|
Sign up to set email alerts
|

How to stop binge drinking and speeding motorists: Effects of relational‐interdependent self‐construal and self‐referencing on attitudes toward social marketing

Abstract: How can marketers stop speeding motorists and binge drinking? Two experiments show that the beliefs consumers have about the degree to which they define themselves in terms of their close relationships (i.e., relational-interdependent self-construal (RISC)) offer useful insights into the effectiveness of communications for two key social marketing issues-road safety (Study 1, New Zealand sample) and alcohol consumption (Study 2, English sample). Further, self-referencing is a mechanism for these effects. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 28 publications
3
28
0
3
Order By: Relevance
“…A second major contribution of this research is the fact that it studies the impact of communication strategies in combating aggressive driving. A limited number of prior studies have examined the effectiveness of ads targeted at aggressive driving (Elliott & Armitage, ; Martin et al, ; Millar & Millar, ; Mowen et al, ). Study 2 examines the interaction between drivers' regulatory focus and two commonly used message framing strategies and finds support for the effectiveness of gain‐framed messages in targeting promotion‐oriented drivers—those most at risk to drive aggressively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second major contribution of this research is the fact that it studies the impact of communication strategies in combating aggressive driving. A limited number of prior studies have examined the effectiveness of ads targeted at aggressive driving (Elliott & Armitage, ; Martin et al, ; Millar & Millar, ; Mowen et al, ). Study 2 examines the interaction between drivers' regulatory focus and two commonly used message framing strategies and finds support for the effectiveness of gain‐framed messages in targeting promotion‐oriented drivers—those most at risk to drive aggressively.…”
Section: Discussionmentioning
confidence: 99%
“…Because promotion orientation drivers would be expected to show a greater tendency to drive aggressively, a natural question arises: What type of safe driving communication would be effective for these drivers? Despite an increasing number of local and state campaigns targeted at discouraging aggressive driving, there have been only a handful of prior studies on the effects of public service announcements on aggressive driving (Elliott & Armitage, ; Lewis, Watson, White, & Tay, ; Martin, Lee, Weeks, & Kaya, ; Millar & Millar, ; Mowen, Harris, & Bone, ). Given the scarcity of prior work, it is important to review findings from another social marketing area that has received significantly more attention, consumer health decision making.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Within social and health marketing literature, self‐construal has been found to be a significant variable in persuading people to behave in a less risky manner. The argument is that people who define themselves in terms of close attachments or relationships respond positively to messages where a relational element is identified in the message (Chang, ; Martin, Lee, Weeks, & Kaya, ). Along a similar vein, people who perceive strong attachments in their lives suppress or have strong protective factors against involvement in risky behaviours (Young, ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…However, no research into the relationship between CQ and alcohol consumption behaviours has been identified. However, applying CQ to the study of individual behaviour on alcohol is logical because the literature suggests that when one is primed to have a particular SC, it can influence one's attitude towards alcohol consumption (Martin et al, ; Zhang & Shrum, ). We posit that the fundamental cognitive process that influences one's attitudes and behaviour when either self‐construal is made salient is mindfulness, which is the engine that drives cultural metacognition.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Perceived ease of use affects users' attitude toward web application 23,27 and further affects social media 42,43 . If people can easily exchange information with friends via a social networking application, then they will consider the adoption of that application worthwhile 44 .…”
Section: Attitude Toward and Intention To Use Social Mediamentioning
confidence: 99%